One-Pot, Regioselective Synthesis of Homopropargyl Alcohols using Propargyl Bromide and Carbonyl Compound by the Mg-mediated Reaction under Solvent-free Conditions - Ma, Xiaofang; Li, Shunxi; Devaramani, Samrat; Zhao, Guohu; Xu, Daqian (Letters in Organic Chemistry, 2020)
The elimination of volatile organic solvents in organic synthesis is the most important goal in “Green” chemistry. We report a simple, efficient and facile method for the addition of progargyl bromide to carbonyl compounds using Mg metal as a mediator under solvent-free conditions which could regioselectively generate homopropargyl alcohols efficiently in good to excellent yields. The procedure has advantages such as short reaction time, operationally simple, excellent product yields, high regioselectivity and organic solvent-free.
Keywords: homopropargyl alcohol